Keratosis Obturans Management - A.C Romdhoni (Biomolecular and Health Science Journal, 2018)
Keratosis obturans is a large accumulation of plaque from desquamated keratin distributed in the ear. The etiology of keratosis obturans remains unclear. Keratosis obturans generally occurs in young patients between the ages of 5-20 years and can attack one or both ears. Patients suffering from keratosis obturans and have a history of bronchiectasis or sinusitis reported 77% of adolescent cases, only 20% of adult cases. The diagnosis of keratosis obturance is made on the basis of anamnesis and clinical examination, while CT scan is performed to determine whether or not bone erosion is present. This disease can be controlled by performing clearance of the ear canal periodically every one to three months to reduce debris accumulation. Ear dropping of mixtures of alcohol or glycerin in 3% peroxide, three times a week can often be helpful.